Molecular and active-site structure of a Bacillus 1,3-1,4-beta-glucanase. - Keitel, T (1993)
The three-dimensional structure of the hybrid Bacillus 1,3-1,4-beta-glucanase (beta-glucanase; 1,3-1,4-beta-D-glucan 4-glucanohydrolase, lichenase, EC 3.2.1.73) designated H(A16-M) was determined by x-ray crystallography at a resolution of 2.0 A and refined to an R value of 16.4% using stereochemical restraints. The protein molecule consists mainly of two seven-stranded antiparallel beta-pleated sheets arranged atop each other to form a compact, sandwich-like structure. A channel crossing one side of the protein molecule accommodates an inhibitor, 3,4-epoxybutyl beta-D-cellobioside, which binds covalently to the side chain of Glu-105, as seen in a crystal structure analysis at 2.8-A resolution of the protein-inhibitor complex (R = 16.8%). That Glu-105 may be indispensible for enzyme catalysis by H(A16-M) is suggested by site-directed mutagenesis of this residue, which inevitably leads to an inactive enzyme.